Targeting triglycerides to lower residual cardiovascular risk. (4th March 2022) - Bubb, Kristen J.; Nelson, Adam J.; Nicholls, Stephen J.
ABSTRACT: Introduction: Dyslipidemia therapeutics have primarily focused on lowering levels of low-density lipoprotein cholesterol. However, many patients continue to experience cardiovascular events, despite effective lowering of LDL-C. This has prompted efforts to target additional risk factors to achieve more effective prevention of cardiovascular disease. Emerging evidence suggests that triglyceride rich lipoproteins play a causal role in atherosclerosis, highlighting the potential for specific therapeutic lowering. Areas covered: (1) Evidence to support the causal role of triglyceride rich lipoproteins in atherosclerotic cardiovascular disease. (2) Use of existing lipid modifying therapies to target triglyceride rich lipoproteins. (3) Development of novel therapeutic agents that target triglyceride rich lipoproteins and their potential impact on cardiovascular risk. Expert Opinion/Commentary: Evidence from preclinical, observational and genetic studies highlight the role of triglyceride rich lipoproteins in the causal pathway of atherosclerotic cardiovascular disease. A number of existing agents have the potential to reduce residual cardiovascular risk associated with hypertriglyceridemia. However, emerging agents have the potential to substantially and preferentially lower triglyceride levels beyond contemporary therapeutics. How they will modulate cardiovascular risk will ultimately be determined by large clinical outcomes trials. They do provide the opportunity to substantially influence the way we target dyslipidemia in the prevention of cardiovascular disease.